Encountering affect capacities, apparatuses, conditions - Anderson, Ben 1972- (An Ashgate Book, 2016)
Since the mid-1990s, affect has become central to the social sciences and humanities. Debates abound over how to conceptualise affect, and how to understand the interrelationships between affective life and a range of contemporary political transformations. In Encountering Affect, Ben Anderson explores why understanding affect matters and offers one account of affective life that hones in on the different ways in which affects are ordered. Intervening in debates around non-representational theories, he argues that affective life is always-already 'mediated' - the never finished product of apparatuses, encounters and conditions. Through a wide range of examples including dread-debility-dependency in torture, ordinary hopes, and precariousness, Anderson shows the significance of affect for understanding life today